Cancer of the anal region. (March 2019) - Valvo, Francesca; Ciurlia, Elisa; Avuzzi, Barbara; Doci, Roberto; Ducreux, Michel; Roelofsen, Felicitas; Roth, Arnaud; Trama, Annalisa; Wittekind, Christian; Bosset, Jean-François
Abstract: Anal canal accounts for 2% of all cancer and its incidence increases with age with a predominance in woman. About 80% of all primary anal canal cancers are squamous; adenocarcinoma arising from the glands or glandular ducts shows a behaviour that is similar to that of the adenocarcinoma of the rectum. Risk factors includes sexually transmitted infection with Human Papillomavirus, cigarette smoking, immunosuppression, and sexual practices. The standard treatment for anal canal is chemo – radiation with a combination of fluoropyrimidines and mitomycin or cisplatin. Salvage surgery may be necessary for residual disease after radiotherapy or chemoradiation, for locoregional relapse and/or for sequelae. In the metastatic setting a multidisciplinary approach is preferred and includes medical treatment, surgery, and RT, if appropriate. Discussing these possible options in the initial stage is of most importance to ensure the best quality of life (QoL) for patients.